Iglesias, identidad y plurirreligiosidad: una mirada al protestantismo histórico. (2016)
The following notes seek to give a thematic stimulus to the identity own perspective of historical Protestantism and the positioning of this tradition before an interfaith dialogue, as just a chance to meet with ourselves, with our protests, our flights and struggles. This will lead us to the obvious question about the situation of contemporary Protestantism and the continuity / discontinuity between the original Protestant project and spirit and the complex reality of the “really existing” Protestantisms. At first a historical-typological approach to Latin American Protestantism is proposed, in order to define a common reference framework, and an understanding of the Protestant identity from the so-called “Protestant principle” is offered; in a second stage a historic evangelical perspective on dialogue and relations of historic Protestantism with believers of other religions is presented.